Renewable resource use with imperfect self-control - Holger Strulik; Katharina Werner (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
We investigate renewable resources when the harvesting agents face self-control problems. Individuals are conceptualized as dual selves. The rational long-run self plans for the infinite future while the affective short-run self desires to maximize instantaneous profits. Depending on the degree of self-control, actual behavior is partly driven by short-run desires. This modeling represents impatience and present bias without causing time inconsistent decision making. In a model of a single harvesting agent (e.g. a fishery), we discuss how self-control problems affect harvesting behavior, resource conservation, and sustainability and discuss policies to curb overuse and potential collapse of the resource due to present-biased harvesting behavior. We then extend the model to several harvesting agents and show how limited self-control exacerbates the common pool problem. Finally, we investigate heterogenous agents and show that there are spillover effects of limited self-control in the sense that perfectly rational agents also behave less conservatively when they interact with agents afflicted by imperfect self-control.
Keywords: D60; D90; Q20; Q50; Q58; O40; 330; self-control; temptation; renewable resource use; sustainability; common pool resource management